Lewicowość i prawicowość. Analiza dynamiki idei w polityce, gospodarce i kulturze - Antsipau, Vadzim (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The distinction between political "left" and "right" remains crucial yet ambiguous and ever-changing. This article provides a historical and geographical analysis of these concepts, tracing their origins from the French Revolution through nineteenth- and twentieth-century debates on political authority and economic models, up to today`s cultural conflicts. Special attention is given to the evolving criteria defining left-wing and right-wing positions, highlighting their dependence on historical context and socio-economic transformations.
Keywords: prawica; lewica; polityka; kultura; społeczeństwo; ekonomika; left-right; politics; culture; society; economics